Analisis Pengaruh Aspek Demografi terhadap Pertumbuhan Ekonomi di Provinsi Sumatera Utara - Cristin Elfrida Manurung; Nurlina Nurlina; Iskandar Iskandar (MAN 4 Kota Pekanbaru, 2026)
This research aims to analyzing the influence of demographic factors based on economic growth in North Sumatra Province on the period 2010–2025. This research aims to analyzing the effect of population growth rate, dependency ratio, and labor force participation rate regarding to the economic expansion of North Sumatra Province, as well as to project the demographic bonus phenomenon until 2030. This research uses secondary time series data from 2010-2025 collected from the official records of Statistics Indonesia (BPS). The analysis was conducted using multiple linear regression with the help of EViews 9, the Trend Least Squares method, and the geometric method for projections. According to the output, GRDP is negatively and significantly influenced by both population growth rate and dependency ratio, whereas the labor force participation rate exhibits a positive but non-significant effect. On a simultaneous basis, these three factors significantly affect GRDP, with an Adjusted R-Squared coefficient of 70.82%. The 2030 projection results indicate a population growth rate of 1.47%, a dependency ratio of 48.06%, and a participation rate of the 2030 projection results show a population growth rate of 1.47%, a dependency ratio of 48.06%, a labor force participation rate of 75.53%, and a GRDP at current prices of IDR 789.089,01 billion. These findings suggest that North Sumatra Province has the potential to capitalize on the demographic bonus to accelerate economic expansion by elevating human resource capabilities and generating employment opportunities.